(untitled) (Bangladesh Journal of Neuroscience, 2017)
Migraine is the second most primary headache. The prevalence of Migraine is 12% in the general population, including 18% in women and 6% in men. Migraine can start in childhood and adolescence and continue throughout lifespan. It is most prevalent among people in their 30s and 40s. Migraine is a debilitating hemicranial headache that is pulsating, aggravated by movement, nausea, vomiting and having sensitivity to light and sound, with or without aura. It can affect all aspects of life as work and school, parenting and family relationships and personal and leisure time. There are some theory regarding pathogenesis of migraine which includes cortical spreading depression, cortical spreading oligemia, activation of trigeminocervical complex leading to neuroinflammation & release of vasodialating neuropeptides which include calcitonin gene related peptide (CGRP), substance P, vasoactive intestinal polypeptide (VIP), nitric oxide (NO), and pituitary adenylate cyclase activating peptide (PACAP) & genetic factor. CGRP is a potent vasodilator and causes perivascular plasma protein extravasation and nociceptive pain. Newer medications target CGRP both for acute and preventive treatment of migraine. Bangladesh Journal of Neuroscience 2017; Vol. 33 (1): 39-43